Membranes based on poly(vinyl alcohol)/β-cyclodextrin blends - Paduraru, O. M.; Vasile, C.; Patachia, S.; Grigoras, C.; Oprea, A. M. (Polimery, 2010)
Membranes based on poly(vinyl alcohol)/β-cyclodextrin (PVA/β-CD) with various compositions have been prepared by using a series of three freezing/thawing cycles. The membranes were studied with scanning electron microscopy (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC) and also water swelling tests as well as contact angle measurements have been performed. The swelling kinetics of membranes in water at different temperatures have been also evaluated. It was established that the membrane properties are influenced by the β-cyclodextrin (β-CD) content and the pores diameter. The crystalline fraction in PVA/β-CD membranes increases with the increase of β-CD content.